1989
DOI: 10.1111/j.1365-2923.1989.tb00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning the educator role: a course for medical students

Abstract: The design and evaluation of a revised course on educational skills for medical students is described. The overall aim of this elective was to help students develop a working concept of their educator role regarding themselves, their peers, and their patients. The programme comprised 15 2-hour weekly meetings consisting of small-group discussion and exercises around issues of self-learning skills, peer teaching, and the process of patient education. Advanced preparation was promoted by readings and special ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Often tutor training is relatively short and focused before the PAL interaction, although in some cases multiple focused training Peer assisted learning framework sessions are scheduled over a more extended period of time (Sobral 1989;Blatt et al 2000;Culver et al 2003b) or occur on a more regular basis between individual PAL interactions in a series (Matthes et al 2002).…”
Section: Pal Tutorsmentioning
confidence: 98%
See 2 more Smart Citations
“…Often tutor training is relatively short and focused before the PAL interaction, although in some cases multiple focused training Peer assisted learning framework sessions are scheduled over a more extended period of time (Sobral 1989;Blatt et al 2000;Culver et al 2003b) or occur on a more regular basis between individual PAL interactions in a series (Matthes et al 2002).…”
Section: Pal Tutorsmentioning
confidence: 98%
“…Some programmes require potential tutors to have passed all assessments in the relevant subjects (Glynn et al 2006) or to have high academic achievement (Trevino & Eiland 1980;Escovitz 1990;Howman et al 2002;Hurley et al 2003;Forester et al 2004); others ask course organisers to select or recommend suitable tutors (Walker-Bartnick et al 1984;Lake 1999). Some tutors may be required to have completed a course on teaching (Sobral 1989). A few non-medical PAL projects have used tutors with lowerthan-average achievement or learning difficulties (Maher et al 1998;Scruggs & Mastropieri 1998), reporting considerable benefits of PAL participation for these tutors.…”
Section: Pal Tutorsmentioning
confidence: 98%
See 1 more Smart Citation
“…They often have rich life and educational experiences before and during medical school and have been an underutilized resource as teachers of peers. Previous reports have described students in the following teaching roles: peer tutors (Goodfellow and Schofield, 2001;Johansen et al, 1992;Schaffer et al, 1990;Sobral, 1989;Solomon and Crowe, 2001;Trevino and Eiland, 1980;Walker-Bartnick et al, 1984), standardized patients (Fleikert et al, 1992;Gelula, 1998;Harris and Miller, 1990;Sasson et al, 1999), physical diagnosis skills (Barnes et al, 1978;Escovitz, 1990;Flax and Gerrard, 1974;Haist et al, 1997Haist et al, , 1998Ross et al, 1989;Rund et al, 1977), cardiopulmonary resuscitation skills (Mowbray et al, 1987), problem-based learning (Johansen et al, 1992;Solomon and Crowe, 2001) basic sciences (Hendelman and Boss, 1986;Resnick and MacDougall, 1976), peer teachers as part of a learning to teach course (Burns et al, 1996;Craig and Page, 1987;Greenberg and Jewett, 1987;Paiva et al, 1982;Sobral, 1989;Ross et al, 1989) and a student-designed and taught course (Josephson and Whelan, 2002). Few of these reports describe a comprehensive evaluation regarding their efficacy and generalizability.…”
Section: Introductionmentioning
confidence: 96%
“…This instrument features the item 'I would like to take another course like this one', which shows a substantial correlation with the total score for the course valuing section of the inventory. Previous work has shown that CVI's course valuing section is a good measure of the appeal of an educational experience (Sobral 1989).…”
Section: Introductionmentioning
confidence: 99%